3D printing of gels based on xanthan/konjac gums. (August 2020) - García-Segovia, P.; García-Alcaraz, V.; Balasch-Parisi, S.; Martínez-Monzó, J.
Abstract: 3D printing technology is a promising technology with the possibility of use for developing personalised food. To make this technology easier, and readily available for consumers, greater knowledge of the printing conditions and characteristics of food-ink is needed. This paper investigates the printability of gels based on syrup, xanthan, and konjac gums, while affecting printing variables. Those variables include the printing temperature (25 °C and 50 °C) and the composition of the product analysed using rheological and textural characterisation techniques. Also, the link between rheological and textural properties of gels, and printability was analysed. The higher values of G′, G″ and η* correlated to the mixtures with lower syrup concentration, and higher values of xanthan and konjac gum. Syrup, xanthan gum and konjac gum content influenced the textural properties. With the increase of syrup content, the Fmax, Fmean, Area, and slope showed reductions giving more weak gels. Rheological and textural values can define composition of formulations that give rise to valid 3D printed figures. Industrial relevance: There is an increasing market need for customized food products. Three-dimensional (3D) food printing will be developed in the coming years. Undoubtedly, food printing can have many advantages, but whether the market is ready for such a big change and the technology will grow fast enough are the questions. Also it seems to be the right solution to meet the needs of today's consumers who increasingly have too little time to prepare meals on their own, especially in small or single-person households. In the future, ready, healthy meal, tailored to their individual needs, will be waiting when coming home. 3D printed gels can contribute to develop personalised food with specific nutritional characteristics. For example, this kind of gels can be used to manufacture soft foods for the elderly who have problems to swallow. Highlights: Printability of syrup, xanthan, and konjac gels is affected by temperature. Gels printed at 50 °C were less elastic and had greater fluidity. Higher G′, G″, and η* were obtained with greater content of xanthan gum and KGM. Mixture design can help in 3D food printing modelling.